Женщины в игре без правил: романы / Галина Щербакова - Щербакова Галина Николаевна (Вагриус, 2008)
Экземпляры: ф.8 (2008) / Инвентарный номер: 52380 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Щ 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44